Evolução da rede de localidades centrais na Bahia nos séculos XIX e XX: permanências, complexidades e amadurecimento - Gil Carlos Silveira Porto (2014)
This thesis examines the development of the urban network of Bahia through the 19th and 20th centuries. For its construction, it was necessary to appropriate the theoretical and methodological framework of Historical Geography and deepen the understanding of the category geographic network and of the variable migration, since the objective was to relate the effects of population flows and the size of the population quota in structuring the network. It was assumed that the current network of the central locations of Bahia is a historical product, which guided the search to identify sub-periods of time in which these settlements came to occupy a prominent position in the urban spatial organization. The search was expanded also aiming to understand what were the main constraints that impacted the role each center played and plays in the Bahia´s network interactions. For this purpose, initially was consulted a secondary source - a study called Areas of Influence of Cities (REGIC), produced and published by IBGE in 2007 - in which the main hub-municipalities led by Salvador today were identified. So, to find out the degree of past centrality of each one, it was required reading, analyzing and the interpretation of old maps, reports of the province of Bahia´s presidents, of books and articles, and results of censuses in Brazil since 1872. Thus, it was concluded that the current network of locations in Bahia already had a considerable degree of organization in the first half of the nineteenth century, and still maintained strong ties with the territorial physical structure. However, the arrival of the rails, in the late nineteenth century, and of the highways, in the second part of the twentieth century, introduced new dynamics in the spatial structure of the state, which has intensified the internal and external population dispersion, induced changes in regional productive activities and gave light to a group of human settlements spread beyond the Recôncavo Baiano and the coastal strip. At the end of the twentieth century, Bahia was part of a globalized economy, and the period was also marked by the maturation of the urban network, the high degree of municipal urbanization and the beginning of the decrease in absolute command of Salvador, which since its founding has been the main and the central hub of this network.